ICU Difficult Airway Simulation - Amanda Murray; Mojca Konia (Association of American Medical Colleges, 2010)
Abstract This simulation prepares learners to assess, prepare for, and secure the ICU airway; review and practice using the American Society of Anesthesiologists (ASA) Difficult Airway Algorithm; and review the steps necessary to perform a cricothyroidotomy. The simulation is designed to review and strengthen resident airway skills prior to managing potentially difficult airways independently. Unique aspects of the ICU airway and strategies for management are highlighted and discussed. The simulation offers an opportunity to review and practice using the ASA Difficult Airway Algorithm and reviews the cricothyroidotomy procedure.